Kesetaraan Gender dalam Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah: Studi Kasus di MIN 1 Banyumas - Maghfirotun Chanasah (Yayasan Bina Nagari Banyumas, 2025)
This study aims to analyze the implementation of gender equality in the implementationof the Merdeka Curriculum at MIN 1 Banyumas. The Merdeka Curriculum promotesthe principles of inclusivity and equality in the learning process, which includesproviding equal opportunities for students regardless of gender. Although policies andthe curriculum support gender equality, challenges in its practical application are stillfound, both in task distribution and students' perceptions. The task distribution, whichis still based on gender stereotypes, such as female students being more often assigned